Daflon 500mg is used for the treatment of all grades of hemorrhoids - Taher Barzinjy , Saman (Diyala Journal of Medicine, 2024)
Background: Hemorrhoidal diseases are very common diseases found in surgical outpatient clinics, affecting populations all over the world. Treatments for the different grades of hemorrhoids include lifestyle changes, conservative medical therapy, and operative interventions. Objective: To assess the conservative treatment response of all grades of hemorrhoidal disease (grades 1-4) to a venotonic agent (Daflon 500mg). Patients and Methods: This is a prospective observational study of 196 patients with hemorrhoids, conducted during the period from January 2015 to January 2020, All treated with the standard dose of a venotonic agent (Daflon 500mg). An observation of the reduction and disappearance of the signs and symptoms of the different grades of the disease was done at 1, 3, and 6 months. Results: The mean age of the patients was 46.6 (range 14–85) years. The majority (41.84%) were diagnosed with grade III hemorrhoidal disease and 30.1% with grade II disease; Grade I and Grade IV constitute 9.69% and 18.37%, respectively. excellent improvement observed in about 72.45%, temporary response seen in 15.82% of cases. Conclusion: Daflon 500 mg is an effective first-line conservative treatment for all four grades of hemorrhoidal diseases, including grade 4, which has a 44.74% permanent response rate. This medical treatment, in turn, reduces the chance of surgical intervention and its complications.